Evaluation of Berberine as an Adjunct to TB Treatment - Ozturk, Mumin; Chia, Julius E.; Hazra, Rudranil; Saqib, Mohd; Maine, Rebeng A.; Guler, Reto; Suzuki, Harukazu; Mishra, Bibhuti B.; Brombacher, Frank; Parihar, Suraj P. (Frontiers in Immunology, 2021)
Tuberculosis (TB) is the global health problem with the second highest number of deaths from a communicable disease after COVID-19. Although TB is curable, poor health infrastructure, long and grueling TB treatments have led to the spread of TB pandemic with alarmingly increasing multidrug-resistant (MDR)-TB prevalence. Alternative host modulating therapies can be employed to improve TB drug efficacies or dampen the exaggerated inflammatory responses to improve lung function. Here, we investigated the adjunct therapy of natural immune-modulatory compound berberine in the C57BL/6 mouse model of pulmonary TB. Berberine treatment did not affect Mtb growth in axenic cultures; however, it showed increased bacterial killing in primary murine bone marrow-derived macrophages and human monocyte-derived macrophages. Ad libitum berberine administration was beneficial to the host in combination with rifampicin and isoniazid. Berberine adjunctive treatment resulted in decreased lung pathology with no additive or synergistic effects on bacterial burdens in mice. Lung immune cell flow cytometry analysis showed that adjunctive berberine treatment decreased neutrophil, CD11b+ dendritic cell and recruited interstitial macrophage numbers. Late-onset of adjunctive berberine treatment resulted in a similar phenotype with consistently reduced numbers of neutrophils both in the lungs and the spleen. Together, our results suggest that berberine can be supplemented as an immunomodulatory agent depending on the disease stage and inflammatory status of the host.